Recognizing the Hedonism Lifestyle and Its Prevention in the Young Generation through the Application of Pancasila Values and Pancasila Education - Cahyani, Cielo Dewi (Journal of Creativity Student, 2019)
A country cannot avoid the era of globalization in life. Countries that do not want to follow, reject and even avoid the era of globalization are tantamount to shutting themselves out from the international world, which in turn will make it difficult for the country to establish cooperative relations with other countries. The era of globalization certainly has a positive and negative impact, and one of the negative effects is the emergence of an attitude of hedonism among the people. Hedonism is a view of life that considers that the enjoyment and enjoyment of matter are the main purpose of life. Hedonism is often experienced by the younger generation, and without realizing it, the lifestyle of hedonism is contrary to the Pancasila, namely the second and fifth precepts. But before that, we must also know the causes of the hedonism lifestyle so that this lifestyle is in conflict with the Pancasila. The lifestyle of hedonism cannot be eliminated, and therefore, several ways are needed to reduce hedonism lifestyle habits so as not to detach the values of Pancasila itself. In addition, the role of Pancasila education is also important in this regard. And please keep in our mind, sometimes without realizing, our society already has an attitude of hedonism, therefore we also need awareness and introspection with the signs of the emergence of attitudes of hedonism within us.